A ROS-mediated mitochondrial pathway and Nrf2 pathway activation are involved in BDE-47 induced apoptosis in Neuro-2a cells. (October 2017) - Chen, Hongmei; Tang, Xuexi; Zhou, Bin; Zhou, Zhongyuan; Xu, Ningning; Wang, You
Abstract: Our previous study showed that 2, 2′-, 4, 4′-tetrabromodiphenyl ether (BDE-47) is cytotoxic and induces apoptosis in Neuro-2a cells. In the present study, we aimed to investigate whether nuclear factor (erythroid-derived 2)-like 2 (Nrf2), an antioxidant transcriptional regulator of oxidative stress and apoptosis, is involved in this process. The results of toxicological experiments showed that BDE-47 decreased the cellular mitochondrial membrane potential (MMP) and increased cytochrome c release to the cytoplasm, followed by an increase in intracellular caspase-9 and caspase-3 activity, suggesting that a mitochondrial pathway was involved in the apoptotic process. Intracellular reactive oxygen species (ROS) and malondialdehyde (MDA) contents as well as the oxidized/reduced glutathione (GSSG/GSH) ratio were elevated simultaneously in a concentration-dependent manner, indicating that BDE-47 induced oxidative stress. The ROS scavenger N-acetyl-l -cysteine (NAC) not only alleviated the oxidative stress but also blocked apoptosis and the decrease in MMP induced by BDE-47, indicating that the overproduction of ROS participates in a mitochondria-mediated apoptotic pathway. Moreover, BDE-47 stimulated the transcriptional induction of the Nrf-2 gene and induced mRNA expression of the main antioxidant response genes in the Nrf-2 pathway, including heme oxygenase 1 (HO-1), NAD(P)H/quinone oxidoreductase-1 (NQO1), glutamate-cysteine ligase modifier (GCLM) and glutathione peroxidase (GPX). Additionally, NAC and the p38 mitogen activated protein kinase (MAPK) signaling pathway inhibitor SB 203580 greatly reduced Nrf2 and HO-1 induction. We hypothesized that the ROS mediated mitochondrial pathway is involved in the BDE-47-induced apoptosis in Neuro-2a cells and that the Nrf2 pathway helps protect Neuro-2a cells from BDE-47-induced apoptosis. Highlights: BDE-47 induced Neuro-2a cells apoptosis involving mitochondrial signal pathway. BDE-47 induced ROS overproduction magnify the intracellular apoptotic signals. Nrf2 pathway was involved in protecting Neuro-2a cells from BDE-47-induced apoptosis.